2012
DOI: 10.1136/vr.100191
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a pilot bovine viral diarrhoea virus eradication scheme in Somerset

Abstract: Beginning in April 2006, 41 farms were recruited onto a pilot Bovine viral diarrhoea virus (BVDV) eradication programme across the south of England with the majority of study herds concentrated in Somerset. Each herd was assessed and where relevant cleared of persistently infected (PI) animals. Seven farms dropped out before whole herd screening could be performed. Of the remaining 34 farms, 20 (59 per cent) were classified as infected although two of these were initially misclassified as BVDV-free. Over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…This finding is similar to that of Booth and Brownlie (2012), who reported that herd owners had difficulty complying with recommendations regarding double fencing. Herd owners may not always recognise the relationship between the adoption of certain biosecurity measures and improved disease control and eradication outcomes, and/or may perceive these actions too difficult and time consuming to implement (Gunn and others 2008, Heffernan and others 2009).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This finding is similar to that of Booth and Brownlie (2012), who reported that herd owners had difficulty complying with recommendations regarding double fencing. Herd owners may not always recognise the relationship between the adoption of certain biosecurity measures and improved disease control and eradication outcomes, and/or may perceive these actions too difficult and time consuming to implement (Gunn and others 2008, Heffernan and others 2009).…”
supporting
confidence: 87%
“…Challenges in eradicating BVD (bovine viral diarrhoea) include lack of farmer motivation, difficulties in encouraging compliance with biosecurity and testing protocols, and variations in opinions regarding responsibility to eradicate the disease (Gunn and others 2005, Booth and Brownlie 2012). A coordinated approach, industry support, farmer cooperation, achievable targets and effective communication can help support eradication (Lindberg and others 2006, Barrett and others 2011).…”
mentioning
confidence: 99%
“…The changes could be due to the low sensitivity of the MAP ELISA (van Weering et al, 2007), purchase of seropositive animals on open farms, or exclusion of dry or seropositive animals from the BMT testing. Changes in BVDV antigen status during the study period could also be due to a purchase or removal of infected animals from the herd or bulk milk sample at the time of the testing or due to a persistently infected heifer entering the milking herd (Booth and Brownlie, 2012). The observed changes in prevalence of BVDV antigen and antibodies against MAP, together with the results of farmers' perception of disease status, highlight the importance and value of repeated testing in correctly identifying infected herds and, hence, appropriate control measures.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence can be recorded at herd level-proportion of positive herds-or at individual level-proportion of positive individuals. Antibody prevalences have been reported from 47.4 to 100 % at a herd level [23,67] and 14 to 69 % at the individual level [23,71], while antigen or PI prevalences have been reported ranging from 4.4 to 40 % at the herd level [4,67] and 0.3 to 10 % at an individual level [67,76] (Table 1).…”
Section: Pathogenesis and Epidemiology Of Bvdvmentioning
confidence: 99%
“…RT-PCR testing of pooled blood is in routine use for PI detection in Somerset, England [4]. Further efforts to reduce the cost of testing for PI cattle may include stratification of the herd based on production parameters, as all PI animals identified by Hill et al [28] were in the lowest 10-20 % producing animals.…”
Section: Identifying Pi Individuals During the Eradication Phasementioning
confidence: 99%